Risk factors for the existence of attention deficit hyperactivity disorder symptoms in children with autism spectrum disorders - Lamanna AL (Dove Medical Press, 2017)
Anna Linda Lamanna, Francesco Craig, Emilia Matera, Marta Simone, Maura Buttiglione, Lucia Margari Child Neuropsychiatry Unit, Department of Basic Medical Sciences, Neuroscience and Sense Organs, University of Bari “Aldo Moro”, Bari, Italy Abstract: Over the years, several authors have reported symptoms of attention deficit hyperactivity disorder (ADHD) in patients with autism spectrum disorders (ASD); however, studies on the risk factors of ADHD symptoms in children with ASD are lacking. The aim of this cross-sectional study was to identify the risk factors for the development of ADHD symptoms in children with ASD. The sample consisted of 67 children with ASD who were assessed with Conner’s Parent Rating Scale-Revised (CPRS-R), and with a semi-structured detailed interview administered to parents, to collect a series of clinical data such as coexisting somatic and neuropsychiatric problems and familial and pre/peri/postpartum risk factors. We found that 55% of ASD children exceeded the cut-off of CPRS-R Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV), total scale. The univariate analyses showed that children’s age (P=0.048), motor delay (P=0.039), enuresis (P=0.014), allergies (P<0.01), comorbid oppositional defiant disorder (P=0.026) and intellectual disabilities comorbidities (P=0.034) were associated to the CPRS-R DSM-IV total score. Some familial predictors such as neuropsychiatric family history of intellectual disabilities (P=0.003) and psychosis (P=0.039) were related to the CPRS-R DSM-IV total score. In particular, a model including allergies (P=0.000) and family history of psychosis (P=0.03) explained 25% (corrected R2=0.25) of the variance of the DSM-IV ADHD score. In conclusion, we identified some risk factors associated with the development of ADHD symptoms in ASD children that need to be studied further. Keywords: neurodevelopmental disorders, autism spectrum disorders, ASD, attention deficit hyperactivity disorder, ADHD, risk factors